2016
DOI: 10.1021/acschembio.6b00438
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into the Biosynthesis and Detoxification of Fumonisin Mycotoxins

Abstract: Fumonisins, notably FB1, FB2, FB3, and FB4, are economically important mycotoxins produced by a number Fusarium sp. that occur on corn, rice, and sorghum as well as by Aspergillus sp. on grapes. The fumonisin scaffold is comprised of a C18 polyketide backbone functionalized with two tricarballylic esters and an alanine derived amine. These functional groups contribute to fumonisin's ability to inhibit sphingolipid biosynthesis in animals, plants, and yeasts. We report for the first time the isolation and struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…(iii) Oxidative deamination: fumonisn B 4 (FB 4 , 129) was transformed into fumonisins La 4 (Fla 4 , 130) and Py 4 (FPy 4 , 131) through oxidative deamination by Aspergillus sp. Nonaminated Fla 4 (130) and FPy 4 (131) was significantly less toxic in comparison to the fumonisin B mycotoxins, which provided new insight into the mechanism of fumonisin toxicity [106].…”
Section: Detoxification Of Fumonisinsmentioning
confidence: 89%
See 2 more Smart Citations
“…(iii) Oxidative deamination: fumonisn B 4 (FB 4 , 129) was transformed into fumonisins La 4 (Fla 4 , 130) and Py 4 (FPy 4 , 131) through oxidative deamination by Aspergillus sp. Nonaminated Fla 4 (130) and FPy 4 (131) was significantly less toxic in comparison to the fumonisin B mycotoxins, which provided new insight into the mechanism of fumonisin toxicity [106].…”
Section: Detoxification Of Fumonisinsmentioning
confidence: 89%
“…Using a duckweed (Lemna minor) bioassay, both Fla4 (130) and FPy4, (131) were significantly less toxic in comparision to the fumonisin B mycotoxins. This demonstrated that Aspergillus fungi have the ability to produce enzymes that could be used for fumonisin detoxification [106].…”
Section: Deaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond showing a reduction in the toxicity of the final biotransformation product(s), the mechanism of this reduction must also be determined [143,144]. For example, the reduction in DON toxicity due to C3 carbon epimerization was attributed to attenuated binding of 3- epi -DON within the ribosomal peptidyl transferase center [139,140], in addition to increased polarity of 3 - epi -DON and decreased molecular interactions with different cellular targets, such as Fusarium graminearum Tri101 acetyltransferase [145].…”
Section: Strategies and Methodologiesmentioning
confidence: 99%
“…It was found that among five isolates that could degrade CIT without affecting the desirable monacolin K levels, Enterococcus cloacae and Rhizobium borbori were able to decrease CIT from 5 ppm to 1.83 ppm and 2.82 ppm, after 120 hours at 30 °C, respectively (Kanpiengjai, Mahawan, Lumyong, & Khanongnuch, ). Interestingly, also some Aspergillus strains seem to be able to detoxify mycotoxins, in this case through enzyme activity, as it was shown in a study that attested Aspergillus welwitschiae ability to transform fumonisins in nonaminated forms (FPy and FLa), which are much less toxic, addressing possible new approaches in decontamination processes (Burgess, Renaud, McDowell, & Sumarah, ).…”
Section: Experimental Strategies For Decontaminationmentioning
confidence: 98%